Phase relations in the ternary Cu-Ga-In system - Hock, Rainer; et al. (ELSEVIER SCIENCE SA, 2007)
The phase relations of the Cu-Ga-ln system were investigated in a composition range which is relevant for the production of Cu(In,Ga)Se, based thin film solar cells. The alloys CU16(In-1 -gamma Ga gamma)(9), Cu-9(Ga,In)(4) and elemental In could be identified as the equilibrium phases of a ternary subsystem in the Cu-Ga-In phase diagram. The coexisting phases are well developed until 220 degrees C. In the case of Cu9Ga4 it is remarkable that the solubility of In in Cu9Ga4 highly increases with increasing temperature. Consequences for the selenization of metallic Cu-In-Ga precursors are discussed. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: CuInSe2; CuGaSe2; X-ray diffraction; DC-magnetron sputtering; phase equilibria